In the small, small pond eaudiobook - Fleming, Denise (Weston Woods, 2001)
A frog's eye view of life in a pond throughout the seasons. A child explores the wonders of the natural world in this rhyming, beautiful story about the lives of small animals and insects living around a freshwater pond.